The New Keynesian Phillips Curve Tested on OECD Panel Data - Roger Bjørnstad; Ragnar Nymoen (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
Using a panel data set for OECD countries we replicate the typical features of the New Keynesian Phillips curve models (NPCs) that have been estimated on country data. While this corroborates the NPC also on the macro panel data set, a different conclusion is reached when we test whether the NPC encompasses an existing model of inflation which is without feed-forward terms, but which allows for other adjustment factors than the NPC. We find that the NPC?s expected rate of future inflation and real marginal costs are weak explanatory variables, and that their statistical significance in the typical NPC is due to correlation with the equilibrium correction terms that are implied by the existing inflation model. Our results are in line with the relatively few encompassing studies that exist on country and area data.
Keywords: E12; C23; E31; C52; 330; New Keynesian Phillips curve; forward-looking price setting; panel data model; encompassing; New-Keynesian Phillips Curve; Schätztheorie; Panel; OECD-Staaten